PERILAKU LENTUR BALOK CASTELLATED MODIFIKASI DENGAN PENGAKU TULANGAN BAJA DAN KOMPOSIT MORTAR SERTA TULANGAN LONGITUDINAL - , Budi Doloksaribu ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The strength of steel beam in as a structural element can be increased by making it into a castellated beam and combining it with concrete materials resulting in a composite structure. Castellated beams can be modified by using steel reinforced stiffeners which are welded together. This study modifies a castellated beam which is combined with mortar and uses longitudinal reinforcements, in which this type of beam is called a modified castellated beam with steel reinforcements and composited with mortar, steel stiffeners and longitudinal reinforcements. The purpose of this study is to determine the flexural behavior, collapse pattern and the displacement that occurred in a modified castellated beam with composite stiffeners and reinforced steel mortar and longitudinal reinforcements and the results will be compared with the modified castellated beam of previous study. The specimen in this study had an area of (75x275) mm 2 and a span of 2,884 mm. The ratio of the cement and sand was 1: 1.5 with a fas of 0.4 and uses 1.5% of viscocrete-10 to the cement weight. The experiment results obtained a flexural capacity value of 216.315 kN. This value is 13.58% lower compared to modified angle connected beam (Azwanda, 2014) and 30.31% larger compared to the rectangular aperture wire rope (Amelia, 2012) and 19.51% larger to the rectangular aperture reinforcements (Oliveira, 2012). Deflection occurred when the maximum load is equal to 43.19 mm. The efficiency of the experimental beam, in terms of the moment capacity decreased by 12.47% compared to modified angle connected beam (Azwanda, 2014), and increased respectively by 28.63% and 18.08% compared to rectangular aperture wire rope (Amelia, 2012) and rectangular aperture reinforcements (Oliveira, 2012). In terms of weight, it increased respectively by 1.98% and 1.14% compared to modifications angle connector (Azwanda, 2014) and rectangular aperture wire rope (Amelia, 2012), and decreased by 0.86% compared to rectangular aperture reinforcements (Oliveira, 2012).